(E)-2-[(4-Ethoxyphenyl)iminomethyl]-4-methoxyphenol - Özek, Arzu (International Union of Crystallography, 2009)
In the molecule of the title compound, C(16)H(17)NO(3), the aromatic rings are oriented at a dihedral angle of 29.25 (8)°. An intramolecular O—H⋯N hydrogen bond results in the formation of a nearly planar [maximum deviation 0.034 (13) Å] six-membered ring, which is oriented at dihedral angles of 0.91 (1) and 28.91 (12)° with respect to the aromatic rings. The title molecule is a phenol–imine tautomer, as evidenced by C—O, C—N and C—C bond lengths. In the crystal, molecules are linked by intermolecular C—H⋯O hydrogen bonds that generate C(8) chains.